Material poetics in hemispheric America : words and objects 1950-2010 - Kosick, Rebecca (Edinburgh University Press, 2020)
This book examines poets and artists in the Americas during the late twentieth and early twenty-first centuries to show how they worked to make language into material objects and material objects into language. It builds a theory of?material poetics? that provides an alternative account of poetry in hemispheric America. Rebecca Kosick argues that by reframing American poetry to prominently include object-oriented practices within and beyond the United States, material poetry can be seen as representing a significant branch of the American poetic tradition.